PENTINGNYA MANAJEMEN WAKTU BAGI MAHASISWA SEMESTER AKHIR DI TENGAH TUGAS AKHIR - Rosiva Febrian; Atia Nurul Apriliani; Sri Nurhilmi Fauziah; Azlika Avilla Mutia (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
Final-year students often face time pressure when completing their final projects, impacting mental health and academic achievement. This study investigates the importance of time management for final-year students in completing their final projects. Using a literature review method, various articles related to time management and academic achievement were analyzed. The results show that effective time management enhances productivity, reduces stress, and improves project quality. Factors like prioritization, scheduling, and distraction management are crucial for effective time management. Good time management is key to final-year students' success in completing their projects. Therefore, developing effective time management strategies is essential to enhance academic achievement.